24
$\begingroup$

Playing around with Maple I found this identity $$\sum_{k=0}^{n-1}\frac{2k+1}{1-z^{2k+1}}=n\sum_{k=0}^{n-1}\frac{1}{1+z^{k}}$$ where $n$ is a positive integer, $z=\exp(\pi i/n)$. I was able to verify it only numerically. Does anyone know how to prove it?

$\endgroup$
  • $\begingroup$ Are you sure? All the expressions $1/(1+z^k)$ and $1/(1-z^{2k+1})$ have real parts equal to $1/2$ but the coefficients on the left add up to more than $n.$ $\endgroup$ – Justpassingby Dec 18 '15 at 19:40
  • 2
    $\begingroup$ @Justpassingby: The sum of the coefficients on the right is $n^2$, not $n$ (note the $n$ in front of the sum). That matches the sum of the coefficients on the left. So now we have proved that the real parts match! $\endgroup$ – Henning Makholm Dec 18 '15 at 19:46
  • $\begingroup$ @Henning Quite so. That establishes the real part of the equality then :-) $\endgroup$ – Justpassingby Dec 18 '15 at 19:49
  • 1
    $\begingroup$ The imaginary parts then boil down to $$ \sum_{k=0}^{n-1} (2k+1)\tan\left((2k+1-n)\tfrac\pi{2n}\right) = n \sum_{k=0}^{n-1} \tan\left(k\tfrac\pi{2n}\right)$$ $\endgroup$ – Henning Makholm Dec 18 '15 at 20:02
  • $\begingroup$ The RHS has imaginary part 0 baecause the terms for k and n-k cancel out (for k=0 it is real). $\endgroup$ – Justpassingby Dec 19 '15 at 10:27
13
$\begingroup$

First we observe that:

$$\sum_{k=1}^{2n-1} {k\over {1-z^k}} - \sum_{k=1}^{n-1} {2k\over {1-z^{2k}}} = \sum_{k=1}^{n-1} {2k+1 \over {1-z^{2k+1}}} $$

Now, by partial fractions,

$${2k \over {1-z^{2k}}} = {k\over {1-z^k}} + {k\over {1+z^k}} $$ Hence:

$$\sum_{k=1}^{2n-1} {k\over {1-z^k}} - \bigg( \sum_{k=1}^{n-1} {k\over {1-z^{k}}} + \sum_{k=1}^{n-1} {k\over {1+z^{k}}}\bigg) = \sum_{k=1}^{n-1} {2k+1 \over {1-z^{2k+1}}} $$ Now, by combining the first two sums:

$$\sum_{k=n}^{2n-1} {k\over {1-z^k}} - \sum_{k=1}^{n-1} {k\over {1+z^{k}}} = \sum_{k=1}^{n-1} {2k+1 \over {1-z^{2k+1}}} $$

Now let's re-write the first sum:

$$\sum_{k=0}^{n-1} {k+n\over {1-z^{k+n}}} - \sum_{k=0}^{n-1} {k\over {1+z^{k}}} = \sum_{k=1}^{n-1} {2k+1 \over {1-z^{2k+1}}} $$

Now let's use the fact that $z^n=-1$, and combine the final two terms:

$$\sum_{k=0}^{n-1} {n\over {1+z^{k}}} = \sum_{k=1}^{n-1} {2k+1 \over {1-z^{2k+1}}} $$

As required.

$\endgroup$
  • 1
    $\begingroup$ Smart answer. Very nice! +1 $\endgroup$ – Markus Scheuer Dec 23 '15 at 21:41
3
$\begingroup$

Given positive integer $n$ that defines $z := \exp(\pi i/n),$ we can generalize the oddly periodic sum with $$ S_n(x) := \sum_{k=0}^{n-1}\frac{2k+1}{1-xz^{2k+1}}. $$ The power series when $|x| < 1$ is $$ S_n(x) = \sum_{E=0}^{\infty}x^E\sum_{k=0}^{n-1}(2k+1)z^{2kE+E}. $$ This simplifies with the weighted sum, $$ \left.\frac{d}{dr}(\frac{r-r^{2n+1}}{1-r^2})\right|_{r=z^E} = \sum_{k=0}^{n-1}(2k+1)z^{2kE},\ \mbox{ to} $$ $$ S_n(x) = \sum_{E=0}^{\infty}\frac{1-z^{2E}-(2n+1)z^{2En}+(2n+1)z^{2En+2E}+ 2z^{2E}-2z^{2En+2E}}{(1-z^{2E})^2}(xz)^E. $$ We observe that $z^{2E}\to1$ correctly reduces the fraction to $n^2,\ $ the period is (almost) $n,\ $ and $$ S_n(x) = \frac{1}{1+x^n}\left( n^2 - 2n\sum_{E=1}^{n-1} \frac{(xz)^E}{1-z^{2E}} \right). $$ Before we take $x\to1,\ $ we need to recall $$ z=\exp(\pi i/n)\ \implies\ n = 1+\sum_{E=1}^{n-1}\frac{2}{1-z^{2E}}. $$ We can evaluate our analytic sum at $$ S_n(1) = \frac{n}{2}\left(1 + 2\sum_{E=1}^{n-1}\frac{1-z^E}{1-z^{2E}} \right) $$ to find the desired relationship $$ \sum_{k=0}^{n-1}\frac{2k+1}{1-z^{2k+1}}\ =\ \sum_{k=0}^{n-1}\frac{n}{1+z^k}. $$

$\endgroup$
3
$\begingroup$

Your identity is true. I give here the method for you to prove the point for general $n$.

One has as main preliminary remark $$\color{red}{z^n=-1\iff z^{n+k}=-z^k\iff \frac{1}{1-z^k}=\frac{z^{n-k}}{1+z^{n-k}}}$$ We make $$A=\sum_{k=o}^{n-1}\frac{2k+1}{1-z^{2k+1}}$$ $$B=n\sum_{k=0}^{n-1}\frac{1}{1+z^k}$$

Example of algebraic verification: $n=6$, even.

The odd exponents in $A$ are $\begin{cases}1\\3\\5\\7=6+1\\9=6+3\\11=6+5\end{cases}$ therefore $$A=\left({1\over 1-z}+{3\over 1-z^3}+{5\over 1-z^5}\right)+\left({6+1\over 1+z}+{6+3\over 1+z^3}+{6+5\over 1+z^5}\right)$$ $$A=B\Rightarrow \left({1\over 1-z}+{3\over 1-z^3}+{5\over 1-z^5}\right)+\left({1\over 1+z}+{3\over 1+z^3}+{5\over 1+z^5}\right)= 6\left({1\over 1+1}+{1\over 1+z^2}+{1\over 1+z^4}\right)$$ Hence $${2\over 1-z^2}+{6\over 1+1}+{10\over 1-z^{10}}= {6\over 1+1}+{6\over 1+z^2}+{6\over 1+z^4}$$ $${2\over 1-z^2}+{10\over 1+z^4}= {6\over 1+z^2}+{6\over 1+z^4}\iff {1\over 1+z^4}={1-2z^2\over 1-z^4}\iff z^4-z^2+1=0 $$ Since $z^6+1=(z^2+1)(z^4-z^2+1)=0$ the algebraic verification is ended.

Example of algebraic verification: $n=7$, odd.

$$A={1\over 1-z}+{3\over 1-z^3}+{5\over 1-z^5}+{7\over 1+1}+{7+2\over 1+z^2}+{7+4\over 1+z^4}+{7+6\over 1+z^6}=B$$ $$\left({1-6z\over 1-z}-{7\over 1+z}+{7z^2\over 1-z^2}+{2+5z^2\over 1+z^2}+{4\over 1+z^4}\right)={7\over 1+z^3}-{3\over 1-z^3}$$ $$\left({2z(2z^7-z^6+z^5-z^4+6z^3-z^2+z-1)\over z^8-1}\right)={7\over 1+z^3}-{3\over 1-z^3}$$ but the parenthesis equals $${2z(5z^3-2)\over –z-1}$$ because $$\left({2z(2z^7-(\color{red}{z^6-z^5+z^4-z^3+z^2-z+1})+5z^3)\over z^8-1}\right)={2z(5z^3-2)\over –z-1}$$ where the red polynomial is null as a factor of $z^7+1=0$. Therefore $${2z(5z^3-2)\over –z-1}={7\over 1+z^3}-{3\over 1-z^3}= {2(5z^2-2)\over z^6-1}$$ i.e $${z\over –z-1}={1\over z^6-1}\iff z^7-z=-z-1$$ which ends the proof $n=7$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.